SURVIVAL EVALUATION AND SOIL REINFORCEMENT CAPACITY OF FIVE REOPHYTES SPECIES OF THE ATLANTIC RAINFOREST BIOME - Dewes, Junior Joel; Maffra, Charles Rodrigo Belmonte; Sousa, Rita dos Santos; Sutili, Fabrício Jaques (Floresta, 2019)
The aim of this study was to evaluate the survival rate, the vegetative development and vertical pullout resistance of Phyllanthus sellowianus, Salix humboldtiana, Gymnanthes schottiana, Cephallanthus glabratus and Ludwigia elegans propagated by live cuttings. The experiment was conducted at the Federal University of Santa Maria, RS. The experiment was installed in October 2015 and evaluated in June 2016. Experiment was conducted in randomized blocks design with use of 5 plant species and 3 replications. In each block were planted 3 live cuttings of each species, with the total of 45 cuttings for the 3 blocks. The space between plants was of 1 x 1 m. Live cuttings average diameter was 1.7 cm and 60 cm long. Were evaluated the survival rate, morphological variables from shoots, as well as the vertical pullout resistance for each species. The observed survival rates were: P. sellowianus (100%), S. humboldtiana (100%), G. schottiana (83%), %), C. glabratus (67%) e L. elegans (50%), which are statistically different among themselves by Chi-square test (χ ²) at 5% level of significance. The variables, length and diameter of shoots, as well as the vertical pullout resistance are statistically different between species by Tukey’s test at 5% level of significance, and the best results were observed for P. sellowianus and less favorable to L. elegans. The results showed that the evaluated species, excluding L. elegans, had from great to good survival rates. The species P. sellowianus and L. elegans had the major and minor soil mechanical reinforcement capacity, respectively. Keywords: Soil Bioengineering, land reclamation, soil stabilization, vegetative propagation.